ACTH Treatment for Management of Nephrotic Syndrome: A Systematic Review and Reappraisal - Ronith Chakraborty; Arul Mehta; Nikhil Nair; Lena Nemer; Rahul Jain; Hirva Joshi; Rupesh Raina (International Journal of Nephrology, 2020)
Background. In recent years, the use of adrenocorticotropic hormone (ACTH) therapy for treatment of proteinuria due to nephrotic syndrome (NS) has been heavily explored. ACTH therapy, which comes in the natural (H. P. Acthar Gel) or synthetic (tetracosactide) form, has resulted in remission in patients with immunosuppressive and steroid-resistant NS. However, the exact efficacy of ACTH therapy in the NS etiologies, such as membranous nephropathy (MN), focal segmental glomerulosclerosis (FSGS), minimal change disease (MCD), lupus nephritis (LN), IgA nephropathy (IgAN), and membranoproliferative glomerulonephritis (MPGN), has not been determined. Objective. This systematic review analyzed the published literature on ACTH therapy in various NS etiologies to determine its efficacy. Methods. A comprehensive search of MEDLINE, EMBASE, and Cochrane databases was conducted for articles through June 2019. An additional search was performed on clinicaltrials.gov to search for additional trials and cross reference the results of our database search. The literature which studied synthetic or natural ACTH treatment in patients with known etiologies of NS was included. Studies were excluded when they consisted of a single case report or did not analyze the lone effect of ACTH in NS. Results. The initial search yielded a total of 411 papers, and 22 papers were included. In 214 MN patients, there was an overall remission of 40% (85/214) and an overall remission of 43% (42/98) in FSGS patients. In other etiologies, there were overall remissions of 78% (11/14), 31% (5/16), 40% (16/40), and 62% (8/13) in MCD, LN, IgAN, and MPGN patients, respectively. Conclusion. ACTH showed benefits in proteinuria reduction across all etiologies of NS. However, more randomized controlled studies with larger population sets and longer follow-ups are imperative to establish causal benefits. New studies into its efficacy in children are also necessary.